Study of Strain-rate Effect in Two-dimensional Biaxial Test on Granular Material using Discrete Element Method - Ananda Putri Swastinitya; Jessica Sjah; James Jatmiko Oetomo (Indonesian Geotechnical Journal, 2023)
Numerical study to investigate the effect of various strain rates on global friction angle in the sand has been performed. Granular material behavior is influenced by several factors, among others: pack configuration, grain macro and micro roughness, confinement pressure, loading rate, etc. Sand is a granular material composed of discrete particles that the most refined microscopic techniques are needed to study its mechanical properties. In Indonesia, research related to the Discrete Element Method is still very limited. The two-dimensional discrete element method is capable to calculate the motion and interparticle contacts of large number of small particles, and each particle is modeled as a rigid circular element. The study started with the validation of the DEM model using YADE. Particles with a local friction angle of 35° are arranged in a closed rectangular box (frictionless wall). The number of particles used in this model validation simulation is 1000 sphere-type particles with monodisperse particle gradations. The simulation was done by a drained biaxial test with confinement stress of 100 kPa, thereafter varying strain rate are applied. Based on the deviatoric stress–axial strain curve from YADE, the result can be depicted on the Mohr circle to obtain the value of the global friction angle. It is found that the different value of strain rate affects its global friction angle. Increasing the value of the strain rate can increase the material global friction angle, which increases the strain rate from 1% to 5%, 10%, 25%, and 50% will increase its global friction angle by 5%, 5%, 14%, and 18%, respectively.